2019
DOI: 10.1002/mabi.201900148
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose and pH Dual‐Responsive Nanogels for Efficient Protein Delivery

Abstract: Direct delivery of protein suffers from their in vitro and in vivo instability, immunogenicity, and a relatively short half‐life within the body. To overcome these challenges, pH and glucose dual‐responsive biodegradable nanogels comprised of dextran and poly(L‐glutamic acid)‐g‐methoxy poly‐(ethylene glycol)/phenyl boronic acid (PLG‐g‐mPEG/PBA) are designed. The cross‐linked network imparted drug‐loading efficacy of α‐amylase up to 55.6% and hyaluronidase up to 29.1%. In vitro protein release profiles reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The distributions of AAPBA and p(AAPBA) spectra are consistent with that of Li et al. [ 25 , 26 ]. In addition, compared with AAPBA and HPA, the p(AAPBA-b-HPA)2 polymer has a characteristic monomer peak, a peak of the corresponding C C double bond disappears, and a peak of H at a position where the main chain appears, which confirm the occurrence of a polymerisation reaction.…”
Section: Resultssupporting
confidence: 90%
“…The distributions of AAPBA and p(AAPBA) spectra are consistent with that of Li et al. [ 25 , 26 ]. In addition, compared with AAPBA and HPA, the p(AAPBA-b-HPA)2 polymer has a characteristic monomer peak, a peak of the corresponding C C double bond disappears, and a peak of H at a position where the main chain appears, which confirm the occurrence of a polymerisation reaction.…”
Section: Resultssupporting
confidence: 90%
“…The hypoglycemic effect was verified in animal experiments. Si et al developed a novel nanogel system with a particle size of approximately 44 nm based on poly (L-glutamic acid)- g -methoxypoly (ethylene glycol)/aminophenylboronic acid (PLG- g -mPEG/PBA) and dextran ( Figure 7 C) [ 133 ]. The nanogel was constructed through the reversible reaction of boron ester bonds between cis -diol on dextran and phenylboronic acid in PLG- g -mPEG/PBA, and insulin was loaded into the cross-linked lattice during the formation process.…”
Section: Oral Insulin Delivery Nanosystemsmentioning
confidence: 99%
“…The nanogels (CytoC/aNGs) increased the cellular uptake of cytochrome c and improved the intracellular delivery to the targeted sites to induce apoptosis [82]. In another study, pH and glucose dual-responsive biodegradable nanogels were constructed and showed the release of the encapsulated proteins [83]. These nanogels were highly dependent on glucose or pH concentrations, where low amounts of proteins were released in physiological pH or under healthy blood glucose level, while the rapid release was seen at lower pH or under diabetic blood glucose level [83].…”
Section: Delivery Of Peptides or Proteins Using Stimuli-responsive Hydrogelsmentioning
confidence: 99%
“…In another study, pH and glucose dual-responsive biodegradable nanogels were constructed and showed the release of the encapsulated proteins [83]. These nanogels were highly dependent on glucose or pH concentrations, where low amounts of proteins were released in physiological pH or under healthy blood glucose level, while the rapid release was seen at lower pH or under diabetic blood glucose level [83]. Massi et al generated a temperature-sensitive nanogel that responded to matrix metalloproteinase-7 (MMP-7) and with the addition of N-cyclopropylacrylamide (NCPAM) into NIPAM-based copolymer, it allowed the encapsulation of protein cargo and nanogel-crosslinking at slightly elevated temperatures [84].…”
Section: Delivery Of Peptides or Proteins Using Stimuli-responsive Hydrogelsmentioning
confidence: 99%